Luminescent material, luminescent material composition, luminescence conversion member, backlight unit, and liquid crystal display device
By introducing the shell containing organic acid salt ligand and acid groups into the light emitting material of perovskite semiconductor nanoparticles, the problem of insufficient stability of perovskite light emitting material is solved, and a combination of high stability and excellent light emitting performance is achieved.
Patent Information
- Application Number
- JP2020170983
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-10-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-10-09
AI Technical Summary
In the prior art, the stability of perovskite semiconductor nanoparticles is insufficient, making it difficult to achieve long-term high-efficiency light emission in display applications.
A light-emitting material containing a perovskite crystal structure consisting of perovskite semiconductor nanoparticles in the core part, an organic acid ligand with a surface-bound and a shell containing an acid group.
High stability and excellent light emission performance of perovskite-type light emission materials are achieved, especially in blue light emission materials, combining extremely small half-maximum width and high brightness efficiency.
Smart Images

Figure 0007647056000001 
Figure 0007647056000002 
Figure 0007647056000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a luminescent material containing perovskite-type semiconductor nanoparticles, and a luminescent material composition and a wavelength conversion member using the luminescent material. The perovskite-type semiconductor nanoparticles of the present invention have good luminescent properties and can retain the properties for a long period of time. [Background technology]
[0002] Compounds having a perovskite crystal structure are known to have many unique physical properties such as magnetism, piezoelectricity, dielectricity, electroluminescence, and conductivity. In particular, when a perovskite compound having a perovskite crystal structure composed of A, B, and X, where A is a monovalent cation, B is a divalent cation, and X is a monovalent anion, is used as an optical material, it is possible to obtain luminescent colors in almost the entire visible light range from blue to red by changing the type and ratio of X (Non-Patent Documents 1 to 3). Furthermore, the light emitted by the perovskite compounds has a narrow full width at half maximum and high color purity, making them suitable as light-emitting materials and wavelength conversion materials, and they can be used as materials for various light-emitting devices (Patent Documents 1 and 2). However, the perovskite compounds described in Patent Documents 1 and 2 do not have sufficient stability. In addition, in order to improve the stability, complicated post-treatments and steps are required, and the use may be limited to specific applications.
[0003] Patent Document 3 discloses a technique for enhancing stability by dispersing a perovskite compound in a polymer that does not have an acidic group. However, long-term stability cannot be guaranteed by dispersing alone. In addition, Patent Document 3 uses a polymer with a mass 50 times that of the perovskite compound, so that the luminescence intensity per volume is low and the polymer, which is an insulator, is excessive, making it unsuitable for display applications such as wavelength conversion materials and electroluminescence.
[0004] Patent Document 4 discloses a technique for improving stability by treating the surface of a perovskite compound with a special ligand. However, the perovskite compound obtained by this method is not stable for a long time, although it can withstand the device adjustment. In addition, in order to obtain the perovskite compound, many steps such as preparation of a precursor, ligand surface treatment, and multi-stage washing are required, and it is not suitable for a mass production process. Furthermore, although this method is suitable for CsPbBr3 compounds, it is difficult to apply it to perovskite compounds of other compositions.
[0005] Patent Document 5 discloses a technique for enhancing the stability of a perovskite compound by using tri-n-octylphosphine as a ligand compound. However, it is described that, depending on the type of perovskite compound, particle aggregation or phase transition occurs over time, and there is a problem with long-term stability.
[0006] Patent Document 6 relates to an ink composition that contains semiconductor nanoparticles containing a perovskite compound and a curable resin composition, and has high luminescence intensity and solvent resistance of the cured product. In the examples, it specifically discloses an ultraviolet-curable composition that contains a perovskite compound synthesized in the presence of oleic acid and oleylamine, and an acrylic monomer that does not have an acidic group. However, the technical idea of Patent Document 6 is that resistance is imparted only after the composition is irradiated with ultraviolet light to harden the coating material on the surface of the semiconductor nanoparticles, and does not improve the resistance of the semiconductor nanoparticles themselves, so the long-term stability is insufficient.
[0007] Furthermore, as a light-emitting material, particularly for display applications, color purity and the associated expansion of the color gamut are necessary, and therefore an appropriate emission wavelength, emission half-width, and high luminous efficiency are required. However, the material described in Non-Patent Document 4 does not fully satisfy such physical properties as a blue light-emitting material.
[0008] Therefore, there is a demand for a method that can enhance the stability of perovskite compounds alone in a simple manner without relying on post-treatments such as curing or sealing. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2016-132638 A [Patent Document 2] JP 2017-108129 A [Patent Document 3] Special Publication No. 2018-522959 [Patent Document 4] Special Publication No. 2018-530633 [Patent Document 5] JP 2019-016772 A [Patent Document 6] International Publication No. 2019 / 022195 [Non-patent literature]
[0010] [Non-Patent Document 1] Nano Lett.2015,15,3692-3696 [Non-Patent Document 2] J.Am.Chem.Soc.2015,137,10276-10281 [Non-Patent Document 3] Chem.Commun.2016,52,7265-7268 [Non-Patent Document 4] Maerials,2019,12,3845 Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, an object of the present invention is to provide a perovskite compound and a light-emitting material composition which have high stability and excellent light-emitting properties without relying on post-treatment such as curing or sealing, as well as a light-emitting conversion member, a backlight unit, and a liquid crystal display device which have excellent light-emitting properties.
[0012] In particular, the object of the present invention is to provide a light-emitting material that is excellent in both emission half-width and luminous efficiency as a blue light-emitting material. [Means for solving the problem]
[0013] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by the embodiments described below, and have thus completed the present invention.
[0014] An embodiment of the present invention relates to a luminescent material comprising a core containing semiconductor nanoparticles having a perovskite crystal structure, a ligand bound to a surface of the core, and a shell covering at least a portion of the core to which the ligand is bound, wherein the ligand comprises an organic acid salt, and the shell comprises an acidic group-containing compound.
[0015] Another embodiment of the present invention relates to the above light emitting material, wherein the organic acid salt is a fatty acid salt having 1 to 30 carbon atoms.
[0016] Another embodiment of the present invention relates to the above luminescent material, wherein the organic acid salt is a sodium salt.
[0017] Another embodiment of the present invention relates to the above light-emitting material, wherein the acidic group-containing compound contains a copolymer including a monomer unit derived from (meth)acrylic acid.
[0018] Another embodiment of the present invention relates to the above light-emitting material, wherein the copolymer further contains a monomer unit having an oxyalkylene group.
[0019] Another embodiment of the present invention relates to the above light-emitting material, wherein the copolymer further comprises a monomer unit having an alkyl (meth)acrylate.
[0020] Another embodiment of the present invention is a copolymer comprising 100% by mass of the monomers constituting the copolymer, 5 to 40 mass% of a monomer derived from (meth)acrylic acid, 5 to 40% by mass of a monomer having an oxyalkylene group, 10 to 90% by mass of (meth)acrylic acid alkyl ester monomer, The present invention relates to the above light-emitting material, which is a copolymer comprising:
[0021] Another embodiment of the present invention relates to the above light-emitting material, wherein the acidic group-containing compound is a copolymer containing a repeating unit derived from (meth)acrylic acid.
[0022] Another embodiment of the present invention relates to the above light-emitting material, wherein the acidic group-containing compound has a number average molecular weight of 1,000 or more and 15,000 or less.
[0023] Another embodiment of the present invention relates to a luminescent material composition comprising the above-mentioned luminescent material and a solvent.
[0024] Another embodiment of the present invention relates to a wavelength converting member having a wavelength converting layer formed by curing the above light emitting material composition.
[0025] Another embodiment of the present invention relates to a backlight unit including at least the wavelength conversion member and a light source.
[0026] Another embodiment of the present invention relates to a liquid crystal display device including at least the above-described backlight unit and a liquid crystal cell. Effect of the Invention
[0027] The present invention can provide a perovskite compound and a light-emitting material composition which are highly stable and have excellent light-emitting properties without relying on post-treatments such as curing or sealing, as well as a light-emitting conversion member, a backlight unit, and a liquid crystal display device which have excellent light-emitting properties.
[0028] In particular, it is possible to provide a blue light-emitting material that has both an excellent emission half-width and an excellent luminous efficiency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The luminescent material of the present invention comprises a core containing semiconductor nanoparticles having a perovskite crystal structure, a ligand bound to the surface of the core, and a shell covering at least a portion of the core to which the ligand is bound, wherein the ligand comprises an organic acid salt and the shell comprises an acidic group-containing compound. The present invention will be described in detail below.
[0030] <Semiconductor nanoparticles> The semiconductor nanoparticles contained in the core of the luminescent material have a perovskite-type crystal structure whose components are A (monovalent cation), B (divalent cation), and X (monovalent anion including a halide anion). The analysis of the perovskite crystal structure and the molar ratio of A and B (A / B) can be determined based on X-ray photoelectric analysis (hereinafter referred to as XPS). X-ray photoelectric analysis is a suitable method from the viewpoint that each element to be analyzed can be analyzed simultaneously and the measurement accuracy is high. The perovskite crystal structure can be a 0-3 dimensional structure, and a 3 dimensional structure is particularly preferred.
[0031] [A(monovalent cation)] A is a monovalent cation, for example, an ammonium cation (NH + ), and alkylammonium cations with carbon atoms of 6 or less, formamidinium cations (HC(NH2)2 + ), guanidinium cation (C(NH2)3 +), nitrogen-containing organic compound cations such as imidazolium cation, pyridinium cation, and pyrrolidinium cation; or lithium cation (Li + ), sodium cation (Na + ), potassium cation (K + ), rubidium cation (Rb + ), and the cesium cation (Cs + These cations have small ionic diameters and can be inserted into the crystal lattice, allowing the perovskite compound to form a stable three-dimensional crystal.
[0032] A preferred example of an alkylammonium cation having 6 or less carbon atoms is a methylammonium cation (CH3NH3 + ), ethylammonium cation (C2H5NH3 + ), propylammonium cation (C3H7NH3 + ) etc.
[0033] From the viewpoint of obtaining high luminous efficiency, A is preferably a methylammonium cation, a formamidinium cation, or a cesium cation, and from the viewpoint of suppressing color change, A is more preferably a cesium cation. Two or more of these cations may be used in combination.
[0034] When A is a cesium cation, examples of raw materials for the synthesis of semiconductor nanoparticles described below include salts such as cesium chloride, cesium bromide, cesium iodide, cesium hydroxide, cesium carbonate, cesium hydrogen carbonate, cesium bicarbonate, cesium formate, cesium acetate, cesium propionate, cesium pivalate, and cesium oxalate, and an appropriate one can be used depending on the synthesis method. When A is another alkali metal cation, a salt in which the cesium element of the above-mentioned cesium compound is replaced with another alkali metal cation element can be used as the raw material. When A is a nitrogen-containing organic compound cation such as methylammonium cation, for example, a neutral compound other than a salt such as methylamine can be used as a raw material. Two or more of these raw materials may be used in combination.
[0035] [B(divalent cation)] B is a divalent cation, for example, a scandium cation (Sc 2+ ), titanium cation (Ti 2+ ), vanadium cation (V 2+ ), chromium cation (Cr 2+ ), manganese cation (Mn 2+ ), iron cation (Fe 2+ ), cobalt cation (Co 2+ ), nickel cation (Ni 2+ ), copper cation (Cu 2+ ), palladium cation (Pd 2+ ), europium cation (Eu 2+ ), ytterbium cation (Yb 2+ ) or a divalent transition metal cation such as magnesium cation (Mg 2+ ), calcium cation (Ca 2+ ), strontium cation (Sr 2+ ), barium cation (Ba 2+ ), zinc cation (Zn 2+ ), cadmium cation (Cd 2+ ), germanium cation (Ge 2+ ), tin cation (Sn 2+ ), lead cation (Pb 2+ ) and other divalent typical metal cations; Among these, divalent typical metal cations are preferred from the viewpoint of growing stable three-dimensional crystals, more preferably tin cations or lead cations, and particularly preferably lead cations from the viewpoint of obtaining strong luminescence. Two or more of these cations may be used in combination.
[0036] When B is a lead cation, the raw material for the synthesis of the semiconductor nanoparticles described below includes salts such as lead chloride, lead bromide, lead iodide, lead oxide, lead hydroxide, lead sulfide, lead carbonate, lead formate, lead acetate, lead 2-ethylhexanoate, lead oleate, lead stearate, lead naphthenate, lead citrate, lead maleate, and lead acetylacetonate, and an appropriate one can be used depending on the synthesis method. When B is another divalent metal cation, a salt in which the lead element of the above-mentioned lead compound is replaced with another divalent metal cation element can be used as the raw material. Two or more of these raw materials may be used in combination.
[0037] [X(monovalent anion including halide anion)] X is a monovalent anion including a halide anion, and the halide anion is a fluoride anion (F - ), chloride anion (Cl - ), bromide anion (Br - ), iodide anion (I - Among them, chloride anion, bromide anion, or iodide anion are preferred because they form stable three-dimensional crystals and emit strong light in the visible light range. The color of the emitted light is blue when chloride anion is used, green when bromide anion is used, and red when iodide anion is used. Two or more kinds of halide anions may be used in combination. In particular, when chloride anions, bromide anions, and iodide anions are used in combination, the emission wavelength of the semiconductor nanoparticles can be adjusted to a desired wavelength depending on the ratio of the anion species, and an emission spectrum that covers almost the entire range of visible light from blue to red while maintaining a narrow full width at half maximum can be obtained, which is preferable. X may contain a monovalent anion other than a halide anion. Examples of such a monovalent anion include a cyanide anion (CN - ), thiocyanate anion (SCN - ), isothiocyanate anion (CNS - ) and other pseudohalide anions.
[0038] As the raw material for the synthesis of the semiconductor nanoparticles described later, a suitable one can be selected from salts with the above-mentioned A and B as counter cations, such as cesium chloride and lead bromide, and salts with other cations, depending on the synthesis method. Among them, from the viewpoint of the dispersion stability of the raw material and the semiconductor nanoparticles, a salt with tetraalkylammonium as the counter cation is preferable. The four alkyl groups constituting the tetraalkylammonium can each independently be selected from alkyl groups of any carbon length, and may have further substituents such as alicyclic rings, aromatic rings, and polar groups, or the alkyl groups may form a ring together.
[0039] When the raw material of X is a salt of a tetraalkylammonium cation and a halide anion, examples of the raw material of X include salts of chloride anions such as tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, tetrapentylammonium chloride, benzyltriethylammonium chloride, benzyltributylammonium chloride, and (2-methoxyethoxymethyl)triethylammonium chloride; tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrapentylammonium bromide, tetrahexylammonium bromide, tetraheptylammonium bromide, tetraoctylammonium bromide, and tetra(decyl)ammonium bromide. and salts with bromide anions such as tetraethylammonium bromide, tetradodecylammonium bromide, benzyltriethylammonium bromide, benzyltributylammonium bromide, and allyltriethylammonium bromide; and salts with iodide anions such as tetraethylammonium iodide, tetrapropylammonium iodide, tetrabutylammonium iodide, tetrapentylammonium iodide, tetrahexylammonium iodide, tetraheptylammonium iodide, tetraoctylammonium iodide, ethyltripropylammonium iodide, benzyltriethylammonium iodide, benzyltributylammonium iodide, triethylphenylammonium iodide, and 5-azoniaspiro[4.4]nonane iodide. These raw materials may be used in combination of two or more different types.
[0040] Specific examples of the semiconductor nanoparticles having the above-mentioned perovskite crystal structure include the structures described in paragraphs 0036 to 0038 of [Patent Document 6] International Publication No. WO 2019 / 022195, but the present invention is not limited to these.
[0041] The semiconductor nanoparticles in the present invention can be produced by a hot injection method in which raw material liquids are mixed at high temperatures and then rapidly cooled after the generation of fine particles to obtain a stable product, a ligand-assisted reprecipitation method in which fine particles are obtained by reprecipitation utilizing the difference in the miscibility of the product with the solvent, a room temperature synthesis method in which a raw material mixture of A and B, which is a non-halogenated material that does not contain a component that becomes X, is mixed with a separately prepared raw material liquid of X to obtain fine particles under mild conditions at about room temperature, a mechanochemical method in which solid raw materials are reacted by mechanical mixing such as milling or ultrasonic treatment to obtain product fine particles, and in the case of electronic devices, an in situ synthesis method in which a raw material liquid is applied to a substrate and then directly crystallized to obtain a reactant. Among these, the room temperature synthesis method is preferably used from the viewpoint of stable production of fine particles.
[0042] Specific synthetic methods are described in ACS Nano, 10(3), 3648-3657 (2016), Adv. Funct. Mater., 26(15), 2435-2445 (2016), Chem. Commun., 52(45), 7265-7268 (2016), ACS Nano, 10(8), 7943-7954 (2016), Adv. Funct. Mater., 26(47), 8757-8763 (2016), ChemistrySelect, 1(13), 3479-3482 (2016), Adv. Funct. Mater., 26(34), 6238-6245 (2016), Phys. Chem. Lett., 8(7), 1610-1614. (2016), JP 2018-104685 A, WO 2017 / 106979 A, WO 2016 / 180364 A, WO 2017 / 166871 A, WO 2017 / 020137 A, WO 2017 / 077523 A, WO 2018 / 168638 A, JP 2017-108129 A, JP 2017-142486 A, WO 2019 / 022195 A, WO 2019 / 142089 A, etc., described in the synthesis method, but is not limited thereto.
[0043] <Ligand> The luminescent material of the present invention is characterized in that it has a ligand bound to the surface of a core containing a semiconductor nanoparticle having a perovskite crystal structure, and contains an organic acid salt as the ligand. The ligand can improve the stability of the dispersion stability, the spectral characteristics, etc. Examples of the organic acid in the organic acid salt include organic compounds having a carboxyl group and organic compounds having a sulfo group, and from the viewpoint of synthesis, organic compounds having a carboxyl group are preferred. Preferred examples of the organic compounds having a carboxyl group include branched or linear fatty acid salts having 1 to 30 carbon atoms, which may be either saturated or unsaturated.
[0044] Specific examples of linear saturated fatty acid salts include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, and lacteric acid. Examples of linear unsaturated fatty acids include acrylic acid, crotonic acid, isocrotonic acid, undecylenic acid, oleic acid, elaidic acid, cetoleic acid, erucic acid, nervonic acid, sapienic acid, brassidic acid, sorbic acid, linoleic acid, linolenic acid, stearidonic acid, eicosapentaenoic acid, docosapentaenoic acid, docosahexaenoic acid, arachidonic acid, propiolic acid, stearic acid, palmitoleic acid, vaccenic acid, and paulic acid.
[0045] Examples of branched fatty acids include 2-ethylhexanoic acid, 2-ethylisohexanoic acid, 2-propylheptanoic acid, 2-butyloctanoic acid, 2-isobutylisooctanoic acid, 2-pentylnonanoic acid, 2-isopentylnonanoic acid, 2-hexyldecanoic acid, 2-hexylisodecanoic acid, 2-butyldodecanoic acid, 2-isobutyldodecanoic acid, 2-heptylundecanoic acid, and 2-isoheptylundecanoic acid. Canoic acid, 2-isoheptylisoundecanoic acid, 2-dodecylhexanoic acid, 2-isododecylhexanoic acid, 2-octyldodecanoic acid, 2-isooctyldodecanoic acid, 2-octylisododecanoic acid, 2-nonyltridecanoic acid, 2-isononylisotridecanoic acid, 2-decyldodecanoic acid, 2-isodecyldodecanoic acid, 2-decylisododecanoic acid, 2-decyltetradecanoic acid, 2-octylhexadecanoic acid Canic acid, 2-isooctylhexadecanoic acid, 2-undecylpentadecanoic acid, 2-isoundecylpentadecanoic acid, 2-dodecylheptadecanoic acid, 2-isododecylisoheptadecanoic acid, 2-decyloctadecanoic acid, 2-decylisooctadecanoic acid, 2-tridecylheptadecanoic acid, 2-isotridecylisoheptadecanoic acid, 2-tetradecyloctadecanoic acid, 2-isotetradecyloctadecanoic acid Decanoic acid, 2-hexadecylhexadecanoic acid, 2-hexadecyltetradecanoic acid, 2-hexadecylisohexadecanoic acid, 2-isohexadecylisohexadecanoic acid, 2-pentadecylnonadecanoic acid, 2-isopentadecylisononadecanoic acid, 2-tetradecylbehenic acid, 2-isotetradecylbehenic acid, 2-tetradecylisobehenic acid, and 2-isotetradecylisobehenic acid. Examples of tertiary fatty acids include pivalic acid, neononanoic acid, neodecanoic acid, and isononanoic acid.
[0046] Among these, from the viewpoints of solubility in solvents, stability, etc., straight-chain fatty acids are preferred, more preferably at least one selected from caproic acid, enanthic acid, caprylic acid, myristic acid, stearic acid, and oleic acid, and even more preferably oleic acid, which is a straight-chain unsaturated fatty acid.
[0047] These organic acids may be used alone or in combination of two or more.
[0048] The salt component in the organic acid salt is not particularly limited as long as it is a metal cation, and is preferably an alkali metal cation or an alkaline earth metal cation, more preferably an alkali metal cation. Of the alkali metal cations, sodium and potassium are preferred, and more preferably sodium.
[0049] The ligand containing the organic acid salt binds to the core through either ionic interaction or physical interaction that fills the defects of the core, and is particularly likely to bind selectively to the perovskite compound. Therefore, when the ligand and the perovskite compound are placed in an environment where they can come into contact with each other, such as in a solution state, the ligand easily binds to the core. Methods for binding the core to the surface of the ligand include a method in which an organic acid salt is directly applied after the core synthesis, or a method in which an organic acid is applied as a precursor during the core synthesis and then converted into an organic acid salt. The ligand may be an organic acid salt used alone or in combination of two or more kinds, and may be used in combination with another known ligand as long as the effect of the above-mentioned ligand is not impaired. The total content of the ligands is preferably 0.1 to 20 mol, more preferably 0.5 to 10 mol, and further preferably 1 to 5 mol, per mol of A (monovalent cation) in the semiconductor nanoparticles.
[0050] <shell> The luminescent material of the present invention is characterized in that at least a part of the core to which the ligand is bound is covered with a shell containing an acidic group-containing compound. The shell more firmly fixes the ligand, thereby significantly improving not only the stability of the luminescent material but also the luminescent properties.
[0051] Examples of the acidic group of the acidic group-containing compound include a carboxyl group, a sulfo group, a phosphoric acid group, and a phenolic hydroxyl group. In terms of availability of raw materials, synthesis, and functionality as a shell, a carboxyl group is particularly preferred. The acidic group-containing compound is not particularly limited as long as it is a compound containing the above-mentioned acidic group, and may be either a low molecular weight compound or a high molecular weight compound.
[0052] Examples of the acidic group-containing low molecular weight compound include saturated or unsaturated carboxylic acids having 1 to 30 carbon atoms. Examples of the acidic group-containing polymer compound include polymers, copolymer resins, and synthetic rubbers, such as poly(meth)acrylates, poly-α-alkyl acrylates, polyamides, polyvinyl acetals, polyformaldehydes, polyurethanes, polycarbonates, polystyrenes, polyvinyl esters, polyesters, polyvinyl chloride, polyepoxies, cellulose derivatives (e.g., ethyl cellulose, cellulose acetate, nitrocellulose), vinyl chloride-vinyl acetate copolymers, polyamide resins, diallyl phthalate resins, silicone resins, and butadiene-acrylonitrile copolymers, which have the above-mentioned acidic groups.
[0053] The acidic group-containing compound is preferably a polymeric compound from the viewpoint of its function as a shell, and is preferably a poly(meth)acrylate, more preferably a copolymer containing a monomer unit derived from (meth)acrylic acid, from the viewpoint of its function as a shell and resin design.
[0054] As a copolymerization component other than (meth)acrylic acid constituting the copolymer containing a monomer unit derived from (meth)acrylic acid, a known polymerizable monomer can be used, and one or more kinds may be used in any ratio. The content of (meth)acrylic acid relative to 100 parts by mass of all monomers constituting the copolymer is preferably 1 to 99 parts by mass, more preferably 5 to 60 parts by mass, and further preferably 10 to 40 parts by mass. As the monomer, the following ones are preferable, but are not limited thereto.
[0055] Examples of the known polymerizable monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, cetyl (meth)acrylate, decyl (meth)acrylate, and isodecyl (meth)acrylate. (p) linear or branched alkyl (meth)acrylates such as acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, behenyl (meth)acrylate, isomyristyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, and adamantyl (meth)acrylate;
[0056] cyclic alkyl (meth)acrylates or cyclic alkenyl (meth)acrylates such as cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and isobornyl (meth)acrylate;
[0057] (meth)acrylates having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-chloropropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-allyloxypropyl (meth)acrylate, 2-hydroxy-3-allyloxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, glycerin mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, 4-hydroxyvinylbenzene, polypropylene glycol mono(meth)acrylate, and caprolactone adducts of these monomers (the number of moles added is 1 to 5);
[0058] (fluoroalkyl (meth)acrylates such as 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H-hexafluoroisopropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, 1H,1H,2H,2H-heptadecafluorodecyl (meth)acrylate, 2,6-dibromo-4-butylphenyl (meth)acrylate, 2,4,6-tribromophenoxyethyl (meth)acrylate, 2,4,6-tribromophenol 3EO adduct (meth)acrylate, and perfluorooctylethyl (meth)acrylate;
[0059] (meth)acrylates having a heterocycle, such as tetrahydrofurfuryl (meth)acrylate, dioxolane (meth)acrylate, acryloylfurfuryl (meth)acrylate, 2-isocyanatoethyl (meth)acrylate modified furfuryl alcohol, 2-isocyanatoethyl (meth)acrylate modified furfurylamine, 2-bromofuran EO adduct (meth)acrylate, and 3-methyl-3-oxetanyl (meth)acrylate;
[0060] (meth)acrylates having an aromatic ring, such as benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, paracumylphenoxyethyl (meth)acrylate, paracumylphenoxypolyethylene glycol (meth)acrylate, and nonylphenoxypolyethylene glycol (meth)acrylate;
[0061] 2-Methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, n-butoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, 1,3-butylene glycol methyl ether (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol mono (meth)acrylate, methoxypolyethylene glycol #400 (meth)acrylate, methoxypolyethylene glycol #100 (meth)acrylate, methoxypolyethylene glycol #1000 (meth)acrylate, methoxypolyethylene glycol #4000 (meth)acrylate, methoxypolyethylene glycol #200 (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxytripropylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethyl carbitol (meth)acrylate, 2-ethylhexyl carbitol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, cresyl polyethylene glycol (meth)acrylate, (meth)acrylic acid-2-(vinyloxyethoxy)ethyl, p-nonylphenoxyethyl (meth)acrylate, p-nonylphenoxypolyethylene glycol (meth)acrylate, glycidyl (meth)acrylate, β-carboxyethyl (meth)acrylate, succinic acid mono(meth)acryloyl acryloyloxyethyl ester, ω-carboxypolycaprolactone mono(meth)acrylate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hexahydrohydrogen phthalate, 2-(meth)acryloyloxypropyl tetrahydrohydrogen phthalate, octoxypolyethylene glycol polypropylene glycol mono(meth)acrylate, lauroxypolyethylene glycol mono(meth)acrylate,(meth)acrylates having an ether group, such as stearoxy polyethylene glycol mono(meth)acrylate, phenoxy polyethylene glycol mono(meth)acrylate, phenoxy polyethylene glycol polypropylene glycol mono(meth)acrylate, polyethylene glycol monomethyl ether (meth)acrylate, nonylphenoxy polyethylene glycol mono(meth)acrylate, nonylphenoxy polypropylene glycol mono(meth)acrylate, nonylphenoxy polyethylene glycol polypropylene glycol mono(meth)acrylate, n-butoxyethyl (meth)acrylate, and 2-ethoxyethyl (meth)acrylate;
[0062] (meth)acrylates having an oxetanyl group, such as 3-(acryloyloxymethyl) 3-methyloxetane, 3-(methacryloyloxymethyl) 3-methyloxetane, 3-(acryloyloxymethyl) 3-ethyloxetane, 3-(methacryloyloxymethyl) 3-ethyloxetane, 3-(acryloyloxymethyl) 3-butyloxetane, 3-(methacryloyloxymethyl) 3-butyloxetane, 3-(acryloyloxymethyl) 3-hexyloxetane, and 3-(methacryloyloxymethyl) 3-hexyloxetane;
[0063] vinyls such as styrene, α-methylstyrene, p-hydroxystyrene, p-chlorostyrene, p-bromostyrene, p-methylstyrene, p-methoxystyrene, pt-butoxystyrene, pt-butoxycarbonylstyrene, pt-butoxycarbonyloxystyrene, 2,4-diphenyl-4-methyl-1-pentenevinyl acetate, vinyl (meth)acrylate, and allyl (meth)acrylate, vinyl acetate, vinyl monochloroacetate, vinyl benzoate, vinyl pivalate, vinyl butyrate, vinyl laurate, vinyl 2-ethylhexanoate, N-vinylcarbazole, and N-vinylpyrrolidone;
[0064] (meth)acrylamides such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dimethylaminoethyl(meth)acrylate, N,N-dimethylaminopropyl(meth)acrylate, N,N-dimethylaminopropylacrylamide, morpholinoethyl(meth)acrylate, N-methylol(meth)acrylamide, diacetone(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, diacetone(meth)acrylamide, and (meth)acryloylmorpholine;
[0065] Nitriles such as (meth)acrylonitrile; Vinyl ethers having an ether group, such as ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, and isobutyl vinyl ether; Fluoroalkyl (meth)acrylates such as trifluoroethyl (meth)acrylate, octafluoropentyl (meth)acrylate, perfluorooctylethyl (meth)acrylate, and tetrafluoropropyl (meth)acrylate;
[0066] Polysiloxane (meth)acrylates such as trade names "Silaplane FM-0711", "Silaplane FM-0721", and "Silaplane FM-0725" manufactured by JNC Corporation, and trade names "X-22-174DX", "X-22-2426", and "X-22-174ASX" manufactured by Shin-Etsu Silicones Co., Ltd.;
[0067] (Meth)acrylates having an isocyanate group such as 2-isocyanate ethyl methacrylate, 2-isocyanate ethyl acrylate, 4-isocyanate butyl methacrylate, and 4-isocyanate butyl acrylate. The isocyanate group also includes a blocked isocyanate group. The blocked isocyanate group refers to an isocyanate group that is protected with another functional group and has reduced reactivity under non-heating conditions, but is deprotected by heating to regenerate an active isocyanate group. Commercially available polymerizable monomers having such blocked isocyanate groups include, for example, 2-[(3,5-dimethylpyrazolyl)carboxyamino]ethyl methacrylate (Karenz MOI-BP, manufactured by Showa Denko Kogyo Co., Ltd.) and 2-(0-[1'methylpropylideneamino]carboxyamino)ethyl methacrylate (Karenz MOI-BM, manufactured by Showa Denko Kogyo Co., Ltd.).
[0068] Furthermore, the above-mentioned copolymer preferably contains a monomer unit having an oxyalkylene group, more preferably a monomer unit having an oxypropylene group or an oxyethylene group, from the viewpoint of optical properties, etc. Specific examples of such monomers include the above-mentioned (meth)acrylates having an ether group, but are not limited thereto.
[0069] Moreover, the above-mentioned copolymer is more preferably a copolymer containing a (meth)acrylic acid alkyl ester monomer unit from the viewpoints of compatibility as a resin, dispersion stability of a light-emitting material as a shell, etc. The alkyl group in the (meth)acrylic acid alkyl ester monomer is preferably a linear or branched alkyl group having 1 to 35 carbon atoms, and more preferably an alkyl group having 6 to 30 carbon atoms. More specifically, examples of the alkyl group include (meth)acrylic acid alkyl ester monomers having a hexyl group, a 2-ethylhexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, a tridecyl group, a tetradecyl group, a hexadecyl group, a behenyl group, a lauryl group, a stearyl group, etc., but are not limited thereto.
[0070] The copolymer preferably contains, in 100% by mass of monomers constituting the above-mentioned copolymer, 5 to 40% by mass of a monomer derived from (meth)acrylic acid, 5 to 40% by mass of a monomer having an oxyalkylene group, and 10 to 90% by mass of a (meth)acrylic acid alkyl ester monomer.
[0071] The copolymer containing a repeating unit derived from (meth)acrylic acid can be produced by a known radical polymerization method, and free radical polymerization, living radical polymerization, or the like can be used. In the living radical polymerization method, side reactions occurring in general radical polymerization are suppressed, and furthermore, the polymerization growth occurs uniformly, so that block polymers and polymers with uniform molecular weights can be easily obtained. Among them, the atom transfer radical polymerization method using an organic halide or a halogenated sulfonyl compound as an initiator and a transition metal complex as a catalyst is preferred in that it can be applied to a wide range of monomers and that a polymerization temperature that can be applied to existing equipment can be adopted. The polymerization temperature can be appropriately adjusted depending on the type of polymerization initiator used and the boiling point of the solvent, and is preferably 20° C. to 150° C., more preferably 40° C. to 120° C., and even more preferably 50° C. to 100° C. The reaction time can be appropriately adjusted depending on the type of polymerization initiator and monomer used, and is preferably 2 to 30 hours, more preferably 3 to 15 hours. The polymerization reaction is desirably carried out under an inert gas atmosphere to prevent coloration and deactivation of the polymerization initiator, and is preferably carried out under a nitrogen gas atmosphere from the viewpoints of ease of availability, cost, and the like, but is not limited thereto.
[0072] As the polymerization initiator, an azo compound or an organic peroxide can be used. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), and dimethyl 2,2'-azobis(2-methylpropionyl). dopionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0073] Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxy 2-ethylhexanoate, t-butyl peroxy neodecanoate, t-butyl peroxy-2-ethylhexanoate, dilauroxy peroxide, peroxy neodecanoate, t-butyl peroxy pivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0074] The polymerization initiator is not limited to the above, and may be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably in the range of 0.001 to 20 parts by mass relative to 100 parts by mass of the total of the polymerizable monomers.
[0075] During polymerization, a chain transfer agent may be used for the purpose of adjusting the molecular weight. The amount of the chain transfer agent used is preferably 0.001 to 15 parts by mass based on 100 parts by mass of the total of the polymerizable monomers. The chain transfer agent is not particularly limited as long as it is a compound capable of adjusting the molecular weight, and known chain transfer agents can be used. For example, octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-hexadecyl mercaptan, n-tetradecyl mercaptan, mercaptoethanol, 1-thioglycerol, thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, stearyl mercaptans such as 3-mercaptopropionate, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), thiomalic acid, octyl thioglycolate, octyl 3-mercaptopropionate, 2-mercaptoethanesulfonic acid, and butyl thioglycolate; Disulfides such as dimethylxanthogen disulfide, diethylxanthogen disulfide, diisopropylxanthogen disulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetrabutylthiuram disulfide; halogenated hydrocarbons such as carbon tetrachloride, methylene chloride, bromoform, bromotrichloroethane, carbon tetrabromide, and ethylene bromide; Secondary alcohols, such as isopropanol, glycerin, etc.; Lower oxides and their salts, such as phosphorous acid, hypophosphorous acid, and their salts (e.g., sodium hypophosphite, potassium hypophosphite), sulfurous acid, hydrogen sulfite, dithionous acid, metabisulfite, and their salts (e.g., sodium hydrogen sulfite, potassium hydrogen sulfite, sodium dithionite, potassium dithionite, sodium metabisulfite, potassium metabisulfite); Other examples include allyl alcohol, 2-ethylhexyl thioglycolate, α-methylstyrene dimer, terpinolene, α-terpinene, γ-terpinene, dipentene, and anisole. These may be used alone or in combination of two or more.
[0076] During polymerization, an organic solvent can be used as a polymerization solvent. Examples of the organic solvent include, but are not limited to, ethyl acetate, n-butyl acetate, isobutyl acetate, n-propyl acetate, toluene, xylene, acetone, hexane, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, propylene glycol monomethyl ether acetate, diethoxydiethylene glycol, and 3-methoxy-1-butanol. Two or more types of polymerization solvents may be mixed together.
[0077] The shell can be formed by coating the semiconductor nanoparticles to which the ligand is bonded. Since the surface of the semiconductor nanoparticles to which the ligand containing an organic acid salt is bonded is weakly basic, the shell containing the acidic group-containing compound is promoted to coat the particle surface by acid-base interaction, and the shell can be easily coated by coexisting in a solution.
[0078] The number average molecular weight (Mn) of the acidic group-containing compound is preferably 500 or more and 50,000 or less, and from the viewpoint of the solubility of the acidic group-containing compound and the optical properties or stability of the perovskite compound coated with the acidic group-containing compound, it is more preferably 1,000 or more and 15,000 or less.
[0079] The coating amount of the acidic group-containing compound is preferably 1 to 10,000 parts by mass, and more preferably 10 to 1,000 parts by mass, per 100 parts by mass of the core and ligand combined.
[0080] <Light-emitting material composition> The light emitting material composition of the present invention contains the above-mentioned light emitting material and a solvent. The solvent is not particularly limited as long as it does not affect the dispersibility or optical properties of the light-emitting material, and any known organic solvent can be used. In addition, since the luminescent material of the present invention has a core protected by a specific ligand and a shell, it can be used in combination with a solvent having such a strong polarity that the surface of the core of a conventional perovskite compound is roughened or destroyed.In addition, since the luminescent material of the present invention has improved solubility mainly due to the action of the shell, it can be used in combination with a solvent in which a conventional perovskite compound is not dissolved.
[0081] [solvent] Specific examples of the solvent include methanol, ethanol, propanol, isopropanol, butanol, isobutanol, sec-butanol, tert-butanol, pentanol, 3-methyl-1,3-butanediol, 1,3-butanediol, 1,3-butylene glycol, octanediol, 2,4-diethylpentanediol, butylethylpropanediol, 2-methyl-1,3-propanediol, 4-hydroxy-4-methyl-2-pentanone, 2-ethyl-1-hexanol, 3,5,5-trimethyl-1-hexanol, isodecanol, isotridecanol, 3-methoxy-3-methyl-1-butanol, 2-methoxybutanol, 3-methoxybutanol, cyclohexanol, furfuryl alcohol, tetrahydrofurfuryl alcohol, benzyl alcohol, methylcyclohexanol, ethylene glycol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, ... diethylene glycol monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, diethylene glycol mono-2-ethylhexyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-tert-butyl ether, ethylene glycol monopropyl ether, ethylene glycol monomethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monobutyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, propylene glycol monophenyl ether, 1,Alcohol-based solvents such as 3-butylene glycol, propylene glycol n-propyl ether, propylene glycol n-butyl ether, diethylene glycol monoethyl ether, dipropylene glycol n-propyl ether, dipropylene glycol n-butyl ether, tripropylene glycol methyl ether, and tripropylene glycol n-butyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, 2-heptanone, 4-heptanone, 3,5,5-trimethyl-2-cyclohexen-1-one, and 3,3,5-trimethylcyclohexanone; methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, tert-butyl acetate, amyl acetate, isoamyl acetate, ethyl 3-ethoxypropionate, ethyl lactate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, dipropylene glycol methyl ether acetate, ethyl ether acetate, 3-methoxy-3-methylbutyl acetate, 3-methoxybutyl acetate, propylene glycol monomethyl acetate, propylene glycol dimethyl acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, cyclohexanol acetate, propylene glycol diacetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monobutyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol diacetate, dipropylene glycol methyl ether acetate, 1,3-butylene glycol diacetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, 1,6-hydroxybenzodiol diacetate and other ester solvents; diethyl ether, cyclopentyl methyl ether, tetrahydrofuran, 1,Ether solvents such as 4-dioxane, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether, diethylene glycol dibutyl ether, tetraethylene glycol dimethyl ether, and polyethylene glycol dimethyl ether; aromatic solvents such as benzene, toluene, ethylbenzene, o-xylene, m-xylene, p-xylene, o-diethylbenzene, m-diethylbenzene, p-diethylbenzene, n-butylbenzene, sec-butylbenzene, and tert-butylbenzene; alicyclic solvents such as cycloheptane and cyclohexane; pentane, hexane, octane, isopropyl alcohol, and the like. Examples of the solvent include, but are not limited to, aliphatic solvents such as isohexane, isooctane, and isononane; chlorine-based solvents such as dichloromethane, chloroform, carbon tetrachloride, chlorobenzene, o-chlorotoluene, m-chlorotoluene, p-chlorotoluene, m-dichlorobenzene, and 1,2,3-trichloropropane; amide-based solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and dimethylacetamide; acetonitrile, dimethylsulfoxide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, isophorone, triacetin, propylene glycol monomethyl ether propionate, and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate. These solvents may be used alone or in combination of two or more.
[0082] The content of the light emitting material in the composition is preferably 0.1 to 90 parts by mass, more preferably 0.5 to 60 parts by mass, and further preferably 1 to 30 parts by mass, based on 100 parts by mass of the composition.
[0083] [Curing component] The light-emitting material composition may further contain a curing component, which causes a polymerization reaction or a crosslinking reaction to proceed, curing the light-emitting material composition and imparting strength and durability to the light-emitting material composition.
[0084] (Polymerization initiator) In the polymerization reaction, a polymerization initiator and a polymerizable compound are generally used in combination. The polymerization initiator is a compound that generates an active species that initiates a polymerization reaction by irradiation with active energy rays or heat, and a known polymerization initiator can be used. The main active species that initiate a polymerization reaction include a radical polymerization initiator that generates a radical and a cationic polymerization initiator that generates an acid, and these may be used in combination.
[0085] Examples of photoradical polymerization initiators that generate radicals by active energy rays include diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl methyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane, oligo[2-hydroxy-2-methyl-1-[4-(1-methylvinyl acetophenones such as 2-hydroxy-1-[4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl]-2-methylpropan-1-one; benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; phosphines such as 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; and other phenyl glyoxylic methyl esters.
[0086] Among the photoradical polymerization initiators, acetophenones such as aminoketones, phosphines, and oxime ester compounds are preferred. These can be used alone or in combination depending on the properties required for the cured product. When using a radical polymerization initiator, the amount used is preferably 0.01 to 100 parts by mass, more preferably 0.1 to 50 parts by mass, based on 100 parts by mass of the total solid content in the composition.
[0087] Examples of the thermal radical polymerization initiator that generates radicals by heat include azo thermal polymerization initiators and organic peroxide polymerization initiators, and two or more of them may be used in combination. Examples of the azo thermal polymerization initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, 2,2'-azobis(N-butyl-2-methylpropionamide), and 2,2'-azobis(N-cyclohexyl-2-methylpropionamide). Examples of the organic peroxide polymerization initiator include benzoyl peroxide (BPO), lauroyl peroxide, di-t-butylperoxyhexahydroterephthalate, t-butylperoxy-2-ethylhexanoate, di-α-cumyl peroxide (DCPO), t-butylperoxyisopropyl carbonate, di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane (DDBH), 2,5,-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 1,1,3,3-tetramethylbutyl hydroperoxide, and t-butyl hydroperoxide.
[0088] The content of the azo thermal polymerization initiator and the organic peroxide polymerization initiator is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and further preferably 1 to 3 parts by mass, based on 100 parts by mass of the total solid content in the composition.
[0089] Examples of the photocationic polymerization initiator that generates an acid upon irradiation with active energy rays include diazonium salts, sulfonium salts, and iodonium salts. Specific examples of the photocationic polymerization initiator include diazonium salts such as benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, and benzenediazonium hexafluoroborate; sulfonium salts such as triphenylsulfonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroborate, 4,4'-bis[bis(2-hydroxyethoxyphenyl)sulfonio]phenylsulfide bishexafluorophosphate, and diphenyl-4-thiophenoxyphenylsulfonium hexafluorophosphate; and iodonium salts such as diphenyliodonium hexafluoroantimonate, diphenyliodonium hexafluorophosphate, bis(4-t-butylphenyl)iodonium hexafluorophosphate, and bis(4-t-butylphenyl)iodonium hexafluoroantimonate. Of these, iodonium salts are preferably used.
[0090] The content of the cationic photopolymerization initiator is preferably 0.1 to 10 parts by mass, and more preferably 1 to 5 parts by mass, based on 100 parts by mass of the total solid content in the composition.
[0091] Examples of the thermal cationic polymerization initiator that generates an acid by heat include diphenyliodonium hexafluoroarsenate, diphenyliodonium hexafluorophosphate, diphenyliodonium trifluoromethanesulfonate, triphenylsulfonium tetrafluoroborate, tri-p-tolylsulfonium hexafluorophosphate, tri-p-tolylsulfonium trifluoromethanesulfonate, bis(cyclohexylsulfonyl)diazomethane, bis(tert-butylsulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, triphenylsulfonium trifluoromethanesulfonate, diphenyl-4-methylphenylsulfonium trifluoromethanesulfonate, diphenyl-2,4,6-trimethylphenylsulfonium-p-toluenesulfonate, and diphenyl-p-phenylthiophenylsulfonium hexafluorophosphate.
[0092] The content of the thermal cationic polymerization initiator is preferably 0.1 to 20 parts by mass, more preferably 1 to 5 parts by mass, based on 100 parts by mass of the total solid content in the composition. When the content is 0.1 part or more, the curing reaction proceeds sufficiently, and when the content is 20 parts or less, coloring and deterioration of various physical properties derived from the thermal cationic polymerization initiator can be suppressed.
[0093] (polymerizable compound) The polymerizable compound may be a radical polymerizable compound or a cationic polymerizable compound, and these may be used in any combination. The radical polymerizable compound refers to a compound having at least one or more radically polymerizable skeletons in the molecule, and includes liquid or solid monomers, oligomers, or polymers at room temperature and normal pressure. The radical polymerizable compound may be used alone or in combination of two or more kinds at any ratio.
[0094] <Radical Polymerizable Compound> Examples of the radical polymerizable compound include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, crotonic acid, isocrotonic acid, and maleic acid, their salts, ester compounds, acid amides, and acid anhydrides, as well as urethane acrylates, acrylonitrile, styrene derivatives, various unsaturated polyesters, unsaturated polyethers, unsaturated polyamides, and unsaturated polyurethanes, but the present invention is not limited to these. Specific examples of the radical polymerizable compound in the present invention are listed below.
[0095] Examples of the radical polymerizable compound include monofunctional alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and benzyl (meth)acrylate; monofunctional hydroxy-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-chloropropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-allyloxypropyl (meth)acrylate, 2-hydroxy-3-allyloxypropyl acrylate, and 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate;
[0096] 2-Methoxyethyl (meth)acrylate, 1,3-butylene glycol methyl ether (meth)acrylate, butoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol #400 (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxytripropylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, phenoxyethyl (meth)acrylate monofunctional ether group-containing (meth)acrylates such as acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, cresylpolyethylene glycol (meth)acrylate, 2-(vinyloxyethoxy)ethyl acrylate, and glycidyl (meth)acrylate; monofunctional carboxyl group-containing (meth)acrylates such as β-carboxyethyl (meth)acrylate, succinic acid mono(meth)acryloyloxyethyl ester, and ω-carboxypolycaprolactone mono(meth)acrylate; Other monofunctional (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, morpholinoethyl (meth)acrylate, trimethylsiloxyethyl (meth)acrylate, diphenyl-2-(meth)acryloyloxyethyl phosphate, 2-hydroxy-1-(meth)acryloxy-3-methacryloxypropane;
[0097] 1,4-Butanediol di(meth)acrylate, 1,6-Hexanediol di(meth)acrylate, Ethylene glycol di(meth)acrylate, Diethylene glycol di(meth)acrylate, Triethylene glycol di(meth)acrylate, Tetraethylene glycol di(meth)acrylate, Polyethylene glycol #200 di(meth)acrylate, Polyethylene glycol #300 di(meth)acrylate, Polyethylene glycol #400 di(meth)acrylate, Polyethylene glycol #600 di(meth)acrylate, Dipropylene glycol di(meth)acrylate, Tripropylene glycol di(meth)acrylate, Tetrapropylene glycol di(meth)acrylate, Polypropylene glycol #400 di(meth)acrylate, Polypropylene glycol #700 di(meth)acrylate, Neopentyl glycol di(meth)acrylate, Neopentyl glycol PO modified di(meth)acrylate, 1,6-Hexanediol bis(2-hydro (meth)acryloyloxy-3-(meth)acryloyloxypropyl) ether, bis(4-(meth)acryloxypolyethoxyphenyl)propane, 1,9-nonanediol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol di(meth)acrylate monobenzoate, bisphenol A di(meth)acrylate, EO modified bisphenol A di(meth)acrylate, PO modified bisphenol A di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate difunctional (meth)acrylates such as ethylenediaminetetraacetate, ...
[0098] Glycerin PO modified tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane EO modified tri(meth)acrylate, trimethylolpropane PO modified tri(meth)acrylate, isocyanuric acid EO modified tri(meth)acrylate, isocyanuric acid EO modified ε-caprolactone modified tri(meth)acrylate, 1,3,5-tri(meth)acryloylhexahydro-s-triazine, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate trifunctional (meth)acrylates such as acrylate tripropionate; tetrafunctional or higher (meth)acrylates such as pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate monopropionate, dipentaerythritol hexa(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, oligoester tetra(meth)acrylate, and tris((meth)acryloyloxy)phosphate;
[0099] Arylates such as allyl glycidyl ether, diallyl phthalate, triallyl trimellitate, and isocyanuric acid triallylate; acid amides such as acrylamide, N-methylol acrylamide, diacetone acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N-isopropyl acrylamide, acryloyl morpholine, methacrylamide, N-methylol methacrylamide, diacetone methacrylamide, N,N-dimethyl methacrylamide, N,N-diethyl methacrylamide, N-isopropyl methacrylamide, and methacryloyl morpholine; ;Styrenes such as styrene, p-hydroxystyrene, p-chlorostyrene, p-bromostyrene, p-methylstyrene, p-methoxystyrene, pt-butoxystyrene, pt-butoxycarbonylstyrene, pt-butoxycarbonyloxystyrene, 2,4-diphenyl-4-methyl-1-pentene;Other vinyl compounds such as vinyl acetate, vinyl monochloroacetate, vinyl benzoate, vinyl pivalate, vinyl butyrate, vinyl laurate, divinyl adipate, vinyl methacrylate, vinyl crotonate, vinyl 2-ethylhexanoate, N-vinylcarbazole, N-vinylpyrrolidone;
[0100] Three-membered ring compounds such as vinylcyclopropanes, 1-phenyl-2-vinylcyclopropanes, 2-phenyl-3-vinyloxiranes, and 2,3-divinyloxiranes; cyclic ketene acetals such as 2-methylene-1,3-dioxepane, dioxolanes, 2-methylene-4-phenyl-1,3-dioxepane, 4,7-dimethyl-2-methylene-1,3-dioxepane, and 5,6-benzo-2-methylene-1,3-dioxepane; Shinzo Yamashita et al., eds., "Crosslinking Agents Handbook," (1981, Daiichi Sankyo Publishing Co., Ltd., 1982); Examples of such compounds include those described in "UV / EB Curing Handbook (Raw Materials)" edited by Kiyomi Kato (1985, Polymer Publishing Association), "New Practical Technology of Photosensitive Resins" edited by RadTech Research Group and Kiyoshi Akamatsu (1987, CMC), "Refinition of Thermosetting Polymers" edited by Tsuyoshi Endo (1986, CMC), "Polyester Resin Handbook" written by Eiichiro Takiyama (1988, The Nikkan Kogyo Shimbun), and "Applications and Markets of UV / EB Curing Technology" edited by RadTech Research Group (2002, CMC).
[0101] As the radical polymerizable compound, in addition to the above-mentioned monomers, oligomers and prepolymers can be used.
[0102] <Cationically polymerizable compound> The cationically polymerizable compound refers to a compound in which polymerization or crosslinking proceeds due to the action of an acid catalyst generated by irradiation with active energy rays or heat. Cationic polymerizable compounds include, for example, various aminoplasts or phenoplasts, i.e., compounds having a methylol group or a substituted methylol group as formaldehyde precursors, such as urea-formaldehyde, melamine-formaldehyde, benzoguanamine-formaldehyde, glycoluril-formaldehyde resins, and monomers or oligomers thereof; methylolated or alkoxydimethylated phenol derivatives that can serve as formaldehyde precursors; compounds having silanol groups; mixtures of polyenes and polythiols; alkoxysilanes; Examples of the compound include epoxy compounds, oxetane compounds, styrenes, vinyl compounds, vinyl ethers, spiro ortho esters, bicyclo ortho esters, spiro ortho carbonates, cyclic ethers, lactones, oxazolines, aziridines, cyclosiloxanes, ketals, cyclic acid anhydrides, lactams, and aryl dialdehydes.
[0103] The cationic polymerizable compound is preferably an epoxy compound, an oxetane compound, or a vinyl ether, more preferably an epoxy compound or an oxetane compound. The polymerization reaction using an epoxy compound or an oxetane compound has a relatively high reactivity and a short curing time, so that the curing process can be shortened. Specific examples of epoxy compounds include bisphenol A type epoxy resins, bisphenol F type epoxy resins, naphthalene type epoxy resins, alicyclic epoxy resins, and aliphatic epoxy resins. Specific examples of oxetane compounds include phenoxymethyl oxetane, 3,3-bis(methoxymethyl)oxetane, 3,3-bis(phenoxymethyl)oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-{[3-(triethoxysilyl)propoxy]methyl}oxetane, di[1-ethyl(3-oxetanyl)]methyl ether, oxetanyl silsesquioxane, phenol novolac oxetane, and 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene. The cationically polymerizable compounds may be used alone or in combination of two or more kinds.
[0104] The amount of the polymerizable compound including the radical polymerizable compound and the cationic polymerizable compound used is preferably 1 to 99 parts by mass, more preferably 3 to 70 parts by mass, and even more preferably 5 to 50 parts by mass, per 100 parts by mass of the composition.
[0105] The light emitting material composition of the present invention may be used in combination with a sensitizer for the purpose of further improving the sensitivity and improving the film properties after reaction and curing. Examples of sensitizers include chalcone derivatives, unsaturated ketones such as dibenzalacetone, 1,2-diketone derivatives such as benzil and camphorquinone, benzoin derivatives, fluorene derivatives, naphthoquinone derivatives, anthraquinone derivatives, xanthene derivatives, thioxanthene derivatives, xanthone derivatives, thioxanthone derivatives, coumarin derivatives, ketocoumarin derivatives, cyanine derivatives, merocyanine derivatives, and oxonol derivatives, and other polymethine dyes, acridine derivatives, azine derivatives, thiazine derivatives, oxazine derivatives, indoline derivatives, azulene derivatives, azulenium derivatives, squarylium derivatives, porphyrin derivatives, tetraphenylporphyrin derivatives, triarylmethane derivatives, tetrabenzoporphyrin derivatives, and tetrapyrazinoporphyrazine derivatives. Examples of the sensitizer include phthalocyanine derivatives, tetraazaporphyrazine derivatives, tetraquinoxalylporphyrazine derivatives, naphthalocyanine derivatives, subphthalocyanine derivatives, pyrylium derivatives, thiopyrylium derivatives, tetraphylline derivatives, annulene derivatives, spiropyran derivatives, spirooxazine derivatives, thiospiropyran derivatives, metal arene complexes, organic ruthenium complexes, or Michler's ketone derivatives, α-acyloxy esters, acylphosphine oxides, methylphenyl glyoxylates, benzyl, 9,10-phenanthrenequinone, camphorquinone, ethyl anthraquinone, 4,4'-diethylisophthalophenone, 3,3', or 4,4'-tetra(t-butylperoxycarbonyl)benzophenone, and 4,4'-diethylaminobenzophenone. These sensitizers can be used alone or in combination of two or more at any ratio as required. The amount of the sensitizer used is preferably 0.01 to 100 parts by mass, and more preferably 0.1 to 50 parts by mass, based on 100 parts by mass of the polymerization initiator.
[0106] Furthermore, the light-emitting material composition can introduce a crosslinked structure into the light-emitting material by including a crosslinking agent. In this case, a compound having a substituent capable of reacting with the crosslinking agent may be used, a substituent capable of reacting with the crosslinking agent may be introduced into the shell compound, or an acidic group such as a carboxyl group of the shell may be reacted with the crosslinking agent. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, amine-based crosslinking agents, and metal chelate-based crosslinking agents, which may be used alone or in combination of two or more kinds.
[0107] The isocyanate-based crosslinking agent is capable of reacting with a hydroxyl group, an amino group, or a carboxyl group, and examples thereof include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hydrogenated tolylene diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, hexamethylene diisocyanate, diphenylmethane-4,4-diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and adducts of these polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms and isocyanurates of these polyisocyanate compounds.
[0108] Epoxy crosslinkers can react with hydroxyl groups, phenolic hydroxyl groups, amino groups, or carboxyl groups, and examples thereof include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, and diglycerol polyglycidyl ether.
[0109] Aziridine-based crosslinking agents can react with carboxyl groups, etc., and examples thereof include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide).
[0110] The melamine-based crosslinking agent can react with a hydroxyl group or an amino group, and examples thereof include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexaptoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, and melamine resins. The aldehyde-based crosslinking agent is capable of reacting with a hydroxyl group or an amino group, and examples thereof include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.
[0111] The amine-based crosslinking agent can react with a carboxyl group, an ester group, a formyl group, an epoxy group, an isocyanate group, or the like, and examples thereof include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetraamine, diethylenetriamine, triethyltetraamine, isophoronediamine, amino resins, and polyamides. Metal chelate crosslinking agents are capable of reacting with hydroxyl groups, amino groups, carboxyl groups, etc., and examples thereof include acetylacetone and acetoacetyl ester coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium.
[0112] The content of the crosslinking agent is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and further preferably 0.1 to 2 parts by mass, relative to 100 parts by mass of the solid content in the light emitting material composition. When it is within the above range, excellent cohesive strength and adhesive strength can be exhibited, and sufficient durability can be obtained.
[0113] The light-emitting material composition may be used in combination with binder resins, dyes, organic and inorganic pigments, pigment dispersants, oxygen scavengers and reducing agents, antifoggants, anti-fading agents, antihalation agents, fluorescent brighteners, surfactants, colorants, extenders, plasticizers, flame retardants, antioxidants, dye precursors, ultraviolet absorbers, foaming agents, anti-fungal agents, antistatic agents, magnetic materials, dispersants, storage stabilizers such as silane coupling agents and quaternary ammonium chlorides, plasticizers, surface tension adjusters, slipping agents, anti-blocking agents, light stabilizers, leveling agents, defoamers, infrared absorbers, surfactants, thixotropic agents, antibacterial agents, fine particles such as silica, and additives that impart various other properties, diluting solvents, and the like, depending on the purpose.
[0114] <Wavelength conversion material> The wavelength conversion member of the present invention has a wavelength conversion layer formed on a substrate by curing the above-mentioned light emitting material composition. Specifically, the light emitting material composition is applied onto a substrate and cured to form a film or sheet.
[0115] [Base material] The substrate is not particularly limited, and examples thereof include inorganic substrates and resin substrates. Examples of inorganic substrates include glass substrates; ceramic substrates; inorganic substrates such as calcium silicate boards, asbestos slate boards, and cement slate boards; and metal substrates such as aluminum boards, copper boards, stainless steel boards, and plated steel boards. Examples of resins for the resin-based substrate include (meth)acrylic resins such as polymethyl methacrylate; styrene-based resins such as polystyrene, polyvinyl toluene, polystyrene, styrene-methyl methacrylate copolymer, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene block copolymer, and poly(p-methylstyrene); polycarbonate; polyarylate; polyethersulfone; polyolefin-based resins such as polyethylene, polypropylene, and ethylene-propylene; cyclic olefin-based resins such as norbornene resin; halogen-containing resins such as vinyl chloride resin and chlorinated vinyl resin; and polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polycyclohexane dimethanol terephthalate. Resins; polyamides such as nylon 6, nylon 66, and nylon 610; cellulose-based resins such as cellulose triacetate, cellulose acetate propionate, and cellulose acetate butyrate; polyacetal-based resins; fluororesins such as polyvinyl fluoride, polyvinylidene fluoride, polychlorotrifluoroethylene, polyethylene tetrafluoroethylene, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer; polyphenylene oxide; polyphenylene sulfide; polyether ether ketone; polyether nitrile; polysulfone; polyether sulfone; polyoxybenzylene; polyamide imide; silicone resins; and the like. From the viewpoint of improving weather resistance and reducing costs, the above-mentioned resins are preferably (meth)acrylic resins, polyolefin-based resins, cyclic olefin-based resins, polyester-based resins, polyamides, cellulose-based resins, and fluororesins, and more preferably polyester-based resins and fluororesins. The thickness of the resin-based substrate is not particularly limited, and is preferably about 10 to 800 μm. These substrates may be subjected to surface treatment such as corona treatment, flame treatment, plasma treatment, etc., as required.
[0116] [Method of forming wavelength conversion layer] The method for forming the wavelength conversion layer is not particularly limited, and examples thereof include a method in which a light emitting material composition is applied onto a substrate, and then pre-dried as necessary, and further, if necessary, heated or irradiated with active energy rays to cure the film. The thickness of the cured wavelength conversion layer is preferably 0.1 to 200 μm, more preferably 1 to 100 μm.
[0117] As the coating method, a known method can be used, and examples thereof include gravure coating, gravure offset, kiss coating, rod coating, reverse gravure coating, roll coating, comma coating, top coating, die coating, knife coating, lip coating, spray coating, spin coating, bar coating, slit coating, gravure printing, offset printing, screen printing, transfer printing, sublimation transfer printing, and inkjet printing.
[0118] Pre-drying is mainly performed to remove the solvent contained in the coating film, and is preferable because pre-drying promotes the subsequent curing reaction and suppresses foaming and other problems caused by rapid drying, making it difficult for film formation defects to occur. Examples of the pre-drying method include vacuum drying under reduced pressure using a vacuum dryer or the like, drying by baking using a convection oven (hot air dryer), an IR oven, a hot plate or the like, or a combination of these methods.
[0119] The heat treatment can be carried out using the same equipment and facilities as those used for pre-drying, by selecting the temperature and time appropriate for the curing reaction.
[0120] The active energy rays in the active energy ray irradiation include heat rays, ultraviolet rays, visible light rays, near infrared rays, electron beams, etc. As a light source for applying active energy rays, a light source having a main wavelength of emission in the wavelength region of 100 to 450 nm is preferable. Examples of such light sources include ultra-high pressure mercury lamps, high pressure mercury lamps, medium pressure mercury lamps, mercury xenon lamps, metal halide lamps, high power metal halide lamps, xenon lamps, pulsed xenon lamps, deuterium lamps, fluorescent lamps, ND-YAG triple harmonic lasers, HE-CD lasers, nitrogen lasers, XE-Cl excimer lasers, XE-F excimer lasers, semiconductor pumped solid lasers, and LED lamp light sources having emission wavelengths of 365 nm, 375 nm, and 385 nm. In this specification, the definitions of ultraviolet rays, visible light, near infrared rays, etc. are based on "Iwanami Physics and Chemistry Dictionary, 4th Edition" edited by Ryogo Kubo et al. (Iwanami, 1987).
[0121] The wavelength conversion member of the present invention may have other layers in addition to the substrate and the wavelength converting layer. Additional layers include, but are not limited to, known barrier layers and light scattering layers to improve stability and optical properties. The barrier layer is preferably transparent from the viewpoint of extracting the emitted light, and may be made of a polymer such as polyethylene terephthalate, a glass film, etc. The light scattering layer is preferably transparent from the viewpoint of extracting the emitted light, and may be made of a layer containing light scattering particles such as silica particles, an amplifying diffusion film, etc.
[0122] The wave energy conversion member of the present invention may be a molded product of a film or sheet having a wavelength conversion layer. The molding method includes, but is not limited to, vacuum molding, compressed air molding, membrane press molding, in-mold molding, insert molding, insert mold molding, overlay vacuum molding, etc.
[0123] <Backlight unit> The backlight unit of the present invention is a device that includes at least the wavelength conversion member and the light source described above, and is a device that irradiates the light emitted by the light source to the wavelength conversion member installed in the subsequent stage, causing the wavelength conversion member to emit light and extracting the light. The backlight unit may further include any layer such as a light reflecting member, a brightness enhancing section, a prism sheet, a light guide plate, and a medium material layer between elements.
[0124] The light source is not particularly limited, and from the viewpoint of causing the semiconductor nanoparticles having a perovskite crystal structure contained in the wavelength conversion material described above to emit light, it is preferable that the light source has an emission wavelength of 600 nm or less. For example, known light sources such as light emitting diodes (LEDs) such as blue light emitting diodes, lasers, and ELs can be used.
[0125] The backlight unit is designed to realize high color reproducibility in the LCD device described below. Blue light having a central emission wavelength in a wavelength band of 430 to 480 nm and having an emission intensity peak with a half-value width of 50 nm or less; green light having a central emission wavelength in a wavelength band of 500 to 600 nm and having an emission intensity peak with a half-value width of 50 nm or less; It is preferable that the LED emits white light having a central emission wavelength in the wavelength band of 600 to 680 nm and a peak emission intensity with a half-width of 50 nm or less.
[0126] One embodiment of the backlight unit uses, for example, a blue light-emitting diode having a central emission wavelength in the wavelength band of 430 to 480 nm as the light source, and semiconductor nanoparticles having a perovskite crystal structure that emit green and red light as the wavelength conversion member, thereby realizing white light by the blue light emitted from the light source and transmitted through the light conversion member, and the red light and green light emitted from the light conversion member. In another embodiment, an ultraviolet light-emitting diode having a central emission wavelength in the wavelength band of 300 nm to 430 nm is used as the light source, and semiconductor nanoparticles having a perovskite crystal structure that emit blue, green, and red light are used as the wavelength conversion member, thereby realizing white light by the blue light, red light, and green light emitted from the light conversion member.
[0127] From the viewpoint of high color reproducibility, it is preferable to use semiconductor nanoparticles having a perovskite crystal structure characterized by emission with a narrow half-width to form blue, green, and red emission, but as long as semiconductor nanoparticles having a perovskite crystal structure are used for at least one color, other luminescent materials such as quantum dots may be used for the other colors. Examples of quantum dots include, but are not limited to, known quantum dots such as cadmium-based and indium-based quantum dots.
[0128] The light reflecting member is not particularly limited, and may be a reflecting film. As the reflecting film, for example, a known reflecting film such as a reflecting mirror, a film of reflecting particles, a reflecting metal film, a reflector, etc. In addition, the backlight unit of the present invention may include a brightness enhancing portion for the purpose of reflecting a part of the light back toward the direction from which the light was transmitted. A prism sheet usually has a base portion and a prism portion, but the base portion may be omitted depending on the adjacent member. The prism sheet can be attached to the adjacent member via any appropriate adhesive layer. The prism sheet is composed of a plurality of unit prisms arranged in parallel, each of which is convex on the opposite side to the viewing side (back side). By arranging the convex portion of the prism sheet facing the back side, the light passing through the prism sheet is easily concentrated. Furthermore, by arranging the convex portion of the prism sheet facing the back side, less light is reflected without entering the prism sheet compared to when the convex portion is arranged facing the viewing side, and a display with high brightness can be obtained. As the light guide plate, for example, a light guide plate having a lens pattern formed on the back side so that light from the lateral direction can be deflected in the thickness direction, or a light guide plate having a prism shape or the like formed on the back side and / or the viewing side can be used. The one or more media included in the media material layer between the elements can include, but are not limited to, vacuum, air, gas, optical material, adhesive, optical adhesive, glass, polymer, solid, liquid, gel, curable material, optical bonding material, index matching or index mismatching material, refractive index gradient material, cladding or anti-cladding material, spacer, silica gel, brightness enhancing material, scattering or diffusing material, reflective or anti-reflective material, wavelength selective material, wavelength selective anti-reflective material, color filter, or any suitable media known in the art.
[0129] <Liquid crystal display device> The liquid crystal display device of the present invention includes at least the backlight unit and the liquid crystal cell described above. The liquid crystal display device may further include a liquid crystal cell, a viewer-side polarizing plate disposed on the viewer side of the liquid crystal cell, and a rear-side polarizing plate disposed on the rear side of the liquid crystal cell. The viewer-side polarizing plate and the rear-side polarizing plate are disposed such that their absorption axes are substantially perpendicular or parallel to each other.
[0130] A liquid crystal cell has a pair of substrates and a liquid crystal layer as a display medium sandwiched between the substrates. In a typical configuration, one substrate is provided with a color filter and a black matrix, and the other substrate is provided with switching elements for controlling the electro-optical properties of the liquid crystal, scanning lines for providing gate signals to the switching elements, signal lines for providing source signals, pixel electrodes, and counter electrodes. The distance between the substrates (cell gap) can be controlled by spacers or the like. An alignment film made of, for example, polyimide can be provided on the side of the substrate that contacts the liquid crystal layer.
[0131] The polarizing plate typically has a polarizer and protective layers arranged on both sides of the polarizer. The polarizer is typically an absorptive polarizer. Any appropriate polarizer is used as the polarizer. For example, a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, or an ethylene-vinyl acetate copolymer partially saponified film is uniaxially stretched after adsorbing a dichroic substance such as iodine or a dichroic dye, or a polyene-based oriented film such as a dehydrated product of polyvinyl alcohol or a dehydrochlorinated product of polyvinyl chloride, etc., can be mentioned. Among these, a polarizer obtained by adsorbing a dichroic substance such as iodine to a polyvinyl alcohol film and uniaxially stretching the film is particularly preferred because it has a high polarization dichroic ratio. EXAMPLES
[0132] The present invention will be described in detail below with reference to examples, but the following examples are not intended to limit the scope of the present invention. Unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass".
[0133] <Number average molecular weight> The number average molecular weight was measured using a GPC (gel permeation chromatography) "GPC-8020" manufactured by Tosoh Corporation. The columns used were two SHODEX KF-806L, one KF-804L, and one KF-802, and the solvent was tetrahydrofuran, with the value calculated in terms of standard polystyrene.
[0134] <Shell: Synthesis of compounds containing acidic groups> (Synthesis example 1: Copolymer (1)) A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a gas inlet tube was charged with 80 parts of toluene as a solvent, and the temperature was raised to 70° C. under a nitrogen atmosphere. Next, a monomer liquid prepared by mixing 10 parts of acrylic acid, 90 parts of octyl methacrylate, 6 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) as an initiator, and 41 parts of toluene was added dropwise over 2 hours, and the mixture was allowed to react at 70°C for 1 hour. Next, 0.6 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added as an additional initiator and reacted for 1 hour until the monomer addition rate reached 98% or more, after which the solid content was adjusted to 50% using toluene to obtain a solution of copolymer (1) containing repeating units derived from (meth)acrylic acid. The number average molecular weight of the obtained copolymer was 10,000.
[0135] (Synthesis Examples 2 to 8, Comparative Synthesis Example 1: Copolymers (2) to (8), Comparative Polymer (1)) Except for changing the monomers to the types and amounts shown in Table 1, the same procedure as in Synthesis Example 1 was carried out to obtain solutions of copolymers (2) to (8) containing repeating units derived from (meth)acrylic acid and comparative polymer (1) not containing repeating units derived from (meth)acrylic acid, each having a solid content of 50%.
[0136] The resulting copolymer is shown below.
[0137] [Table 1]
[0138] <Ligand: Preparation of organic acid salt solution> (Preparation Example 1: Sodium Caproate) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a gas inlet tube, 90 parts of caproic acid and 20 parts of sodium hydroxide were charged, and the temperature was raised to 120°C under reduced pressure, and the mixture was heated for 30 minutes. After confirming that the sodium hydroxide had completely dissolved, the reduced pressure was released and the mixture was placed under a nitrogen atmosphere. After lowering the temperature to 60°C, 110 parts of toluene were charged to obtain a sodium caproate solution.
[0139] (Preparation Example 2: Sodium oleate) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a gas inlet tube, 100 parts of oleic acid and 10 parts of sodium hydroxide were charged, and the temperature was raised to 120°C under reduced pressure, and the vessel was heated for 30 minutes. After confirming that the sodium hydroxide had completely dissolved, the reduced pressure was released and the vessel was placed under a nitrogen atmosphere. After lowering the temperature to 60°C, 120 parts of toluene were charged to obtain a sodium oleate solution.
[0140] (Preparation Example 3: Sodium Lignocerate) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a gas inlet tube, 140 parts of oleic acid and 5 parts of sodium hydroxide were charged, and the temperature was raised to 120°C under reduced pressure, and the mixture was heated for 30 minutes. After confirming that the sodium hydroxide had completely dissolved, the reduced pressure was released and the mixture was placed under a nitrogen atmosphere. After lowering the temperature to 60°C, 140 parts of toluene were charged to obtain a sodium lignocerate solution.
[0141] <Production of Light Emitting Material Composition> [Example 1] (Core synthesis) 1.68 parts of cesium hydroxide, 2.23 parts of lead (II) oxide, and 45 parts of oleic acid were placed in a flask and dissolved by heating to a liquid temperature of 130°C under a dry nitrogen stream. After maintaining the temperature for a while and removing the generated water from the system, 325 parts of toluene that had been dehydrated and degassed with dry nitrogen in advance was added, and the mixture was cooled to room temperature to obtain a cation raw material liquid. Separately, 2.73 parts of tetraoctylammonium bromide, 1.67 parts of tetraamylammonium chloride, and 5.6 parts of oleic acid were dissolved in 32.5 parts of toluene at room temperature to obtain an anion raw material solution. At a liquid temperature of 20° C., under dry nitrogen, the anion raw material liquid was quickly added to the cation raw material liquid and stirred. After 20 seconds, 160 parts of ethanol was added, followed by centrifugation and collection of the supernatant. The same volume of acetone was added to the resulting supernatant, and the mixture was centrifuged again to collect the precipitate. The resulting precipitate was dispersed in toluene to adjust the solids concentration to 5%, yielding a solution of semiconductor nanoparticles with a perovskite-type crystal structure of CsPb(Br / Cl)3.
[0142] (ligand binding) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a gas inlet tube, 20 parts of the semiconductor nanoparticle solution and 100 parts of toluene were placed at room temperature under a nitrogen atmosphere and diluted. Next, 3 parts of sodium oleate solution was added and stirred for 1 hour. After adding 100 parts of acetone, the mixture was centrifuged and the precipitate was collected. The precipitate was dispersed in toluene to adjust the solid content to 5%, and a solution of a compound with a ligand bound to the core surface was obtained.
[0143] (Shell Covering) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a gas inlet tube, 20 parts of the solution of the compound having a ligand bound to the core surface and 100 parts of toluene were placed and diluted at room temperature under a nitrogen atmosphere. Next, 2 parts of the copolymer (2) solution was added and stirred for 1 hour. After 100 parts of acetone was added, the mixture was centrifuged and the precipitate was collected. The precipitate was dispersed in toluene to adjust the solid content concentration to 5%, and a luminescent material composition 1 was obtained that contains the luminescent material of the present invention in which at least a part of the core to which the ligand is bound is covered with an acidic group-containing compound and a solvent.
[0144] [Examples 2 to 8] Light emitting material compositions 2 to 8 were obtained in the same manner as in Example 1, except that the copolymer (2) solution was changed to a solution of the copolymer shown in Table 2.
[0145] [Example 9] The same procedure as in Example 1 was carried out to obtain a luminescent material composition 9, except that the 2.73 parts of tetraoctylammonium bromide and 1.67 parts of tetraamylammonium chloride used in the synthesis of the core in Example 1 were changed to 5.47 parts of tetraoctylammonium bromide to obtain a solution of semiconductor nanoparticles having a perovskite crystal structure of CsPbBr3.
[0146] [Examples 10 to 16] The same procedure as in Example 9 was carried out except that the sodium oleate solution and the copolymer (1) solution were changed to solutions of the compounds shown in Table 2, to obtain light emitting material compositions 10 to 16.
[0147] [Example 17] The same procedure as in Example 1 was carried out to obtain a luminescent material composition 17, except that the 2.73 parts of tetraoctylammonium bromide and 1.67 parts of tetraamylammonium chloride in the core synthesis of Example 1 were changed to 4.82 parts of tetrahexylammonium iodide to obtain a solution of semiconductor nanoparticles having a perovskite crystal structure of CsPbI3.
[0148] [Examples 18 to 24] The same procedure as in Example 17 was carried out except that the sodium oleate solution and the copolymer (1) solution were changed to solutions of the compounds shown in Table 2, to obtain light emitting material compositions 18 to 24.
[0149] [Comparative Example 1] The solution of semiconductor nanoparticles having a perovskite crystal structure of CsPb(Br / Cl) 3 obtained in Example 1 was used as a light emitting material composition 25.
[0150] [Comparative Example 2] The core was synthesized in the same manner as in Example 1 to obtain a solution of semiconductor nanoparticles having a perovskite crystal structure of CsPb(Br / Cl)3. Next, the shell coating process was performed in the same manner as in Example 1, except that the solution of the compound having a ligand bonded to the core surface was changed to the solution of the semiconductor nanoparticles, to obtain a light-emitting material composition 26.
[0151] [Comparative Example 3] A light emitting material composition 27 was obtained in the same manner as in Comparative Example 2, except that the copolymer (2) solution in Comparative Example 2 was changed to a comparative polymer (1) solution.
[0152] [Comparative Example 4] A light emitting material composition 28 was obtained in the same manner as in Example 1, except that the solution of copolymer (2) was changed to a solution of comparative polymer (1).
[0153] [Comparative Example 5] The solution of the compound having a ligand bound to the core surface obtained in Example 1 was used as a light-emitting material composition 29.
[0154] [Comparative Example 6] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a gas inlet tube, 20 parts of the solution of semiconductor nanoparticles obtained in the core synthesis in Example 1 and 100 parts of toluene were placed at room temperature under a nitrogen atmosphere and diluted. Next, 2 parts of tri-n-octylphosphine was added and stirred for 1 hour. After adding 100 parts of acetone, the mixture was centrifuged and the precipitate was collected. The precipitate was dispersed in toluene to adjust the solid content to 5%, and a light-emitting material composition 30 in which a ligand was bonded to the core surface was obtained.
[0155] [Comparative Example 7] The solution of semiconductor nanoparticles having a perovskite crystal structure of CsPbBr 3 obtained in Example 9 was used as a light emitting material composition 31.
[0156] [Comparative Example 8] The solution of semiconductor nanoparticles having a perovskite crystal structure of CsPbI 3 obtained in Example 17 was used as a light emitting material composition 32.
[0157] <Evaluation of Light Emitting Material Composition> The obtained light emitting material-containing composition was subjected to the following evaluations. The results are shown in Table 2.
[0158] [Evaluation of luminescence characteristics] The emission peak wavelength, full width at half maximum, and internal quantum yield (hereinafter referred to as QY) of the light emitting material-containing composition were measured immediately after preparation and after being left standing in air at room temperature (25° C.) for 2 weeks. The emission peak wavelength and full width at half maximum are emission spectrum values from which the internal quantum yield is calculated, and the internal quantum yield is the number of photons of fluorescent emission when the number of excitation photons absorbed by the semiconductor nanoparticles is taken as 1. Each composition containing a light-emitting material was diluted with toluene to give a light absorptance of between 0.2 and 0.3 at the excitation light wavelength, and then the measurement was performed. The measurement conditions are shown below. <Measurement conditions> Measurement equipment: Otsuka Electronics Co., Ltd. Quantum efficiency measurement equipment QE-2000 Excitation light wavelength: 350 nm (emission peak wavelength is less than 450 nm) 400nm (peak emission wavelength is between 450nm and 600nm) 550nm (peak emission wavelength is 600nm or more) Excitation light integration range: Excitation light wavelength ±25nm Emission integral range: (excitation light wavelength + 30) nm to 800 nm
[0159] [Table 2]
[0160] According to Table 2, the composition containing the light-emitting material of the present invention has high quantum efficiency and narrow half-width regardless of the type of core having various wavelengths, and can maintain these properties for a long period of time. In particular, Examples 1 to 8 show a narrow half-width and extremely high internal quantum efficiency as blue light with an emission wavelength of 450 nm. On the other hand, in the compositions including the light-emitting material not having the specific ligand and shell of the present invention, such as Comparative Examples 1, 7, and 8, the internal quantum efficiency immediately after preparation was high only in Comparative Example 7, but was significantly deactivated over time. Moreover, the internal quantum efficiency immediately after preparation was low in Comparative Examples 1 and 8, and was deactivated over time. As in Comparative Examples 2 and 5, the compositions containing the light-emitting material having only the specific ligand of the present invention or only the specific shell of the present invention all had low internal quantum efficiency immediately after preparation and lost activity over time. Furthermore, as in Comparative Examples 3 and 4, the compositions containing a light-emitting material having a polymer that does not have an acidic group in the shell had low internal quantum efficiency immediately after preparation, regardless of the presence or absence of a ligand, and were deactivated over time, indicating that the effects of the present invention are exerted by the combination of the ligand and the shell. Furthermore, as shown in Comparative Example 6, a composition containing a light-emitting material having a known general ligand also had a low internal quantum efficiency immediately after preparation and was deactivated over time. In some comparative examples, the measured values were below the lower limit of the measurement of the device, and no significant values were obtained, so the measurements were not possible. Precipitation and other defects were observed in these samples, suggesting that the quantum efficiency had dropped significantly due to the deactivation and aggregation of the semiconductor nanoparticles.
[0161] Furthermore, a large change in the peak wavelength was confirmed between Example 1 and Comparative Examples 1 and 4, suggesting that the specific ligand and shell of the present invention do not simply protect the core, but act on the core to improve the luminescence properties. Therefore, the luminescent material of the present invention having a specific ligand and shell exhibits luminescence with a narrow half-width and high color purity, and also exhibits unpredictably excellent internal quantum efficiency and long-term stability of the internal quantum efficiency, and has good luminescent properties and stability over time.
[0162] <Manufacturing of wavelength conversion materials> [Examples 25 to 48, Comparative Examples 10 to 13] A light-emitting material composition, a polymerizable compound, a polymerization initiator, and a solvent were mixed according to the composition shown in Table 3 to obtain a curable composition. The obtained curable composition was spin-coated onto a glass substrate (10 cm x 10 cm), and then dried at 80°C for 1 minute using a hot air dryer. Next, the coating was heated in a belt conveyor-type ultraviolet irradiator (high pressure mercury lamp 120 W / cm 2 Using a total light quantity of 400 mJ / cm 2 By irradiating the glass substrate with ultraviolet light so as to form a cured film with a thickness of 10 μm, wavelength conversion members 1 to 28 were obtained.
[0163] <Evaluation of wavelength conversion materials> The obtained wavelength conversion member was subjected to the following evaluations. The results are shown in Table 3.
[0164] [Appearance evaluation and external quantum efficiency evaluation] The obtained wavelength conversion member was visually evaluated for appearance and measured for external quantum efficiency as an initial evaluation. Next, the member was left to stand for one week at a humidity of 70% RH and 25°C in a constant temperature and humidity chamber, and then the appearance was evaluated and the external quantum efficiency was measured in the same manner as in the initial evaluation as an evaluation after aging. The external quantum efficiency was judged according to the following criteria. <Measurement conditions> Measurement equipment: Quantum efficiency measurement system QE-2000 (Otsuka Electronics Co., Ltd.) Excitation wavelength: 450nm, fluorescence integration range: 500-800nm (judgment criteria) 〇: External quantum efficiency is 5% or more △: External quantum efficiency is 1% or more but less than 5% ×: External quantum efficiency is less than 1%
[0165] [Table 3]
[0166] The abbreviations in Table 3 are as follows: Polymerizable compound A: Dipentaerythritol triacrylate ESACURE ONE: "ESACURE ONE" manufactured by Lambertie (photoradical initiator)
[0167] According to the evaluation results, the wavelength conversion member using the luminescent material of the present invention exhibited the effect of suppressing deterioration over time of the appearance and deterioration over time of the external quantum efficiency, compared with the wavelength conversion member using a luminescent material not having the configuration of the present invention. This is presumably because the luminescent material of the present invention has excellent stability without using a barrier layer, etc., due to being coated with a specific ligand and shell. Comparative Examples 10, 11, and 13 had low initial external quantum efficiency, suggesting that degradation of the luminescent material had already progressed during the cured film formation process, but no such degradation was observed in Examples 25 to 48 of the present invention. Thus, the luminescent material of the present invention has the stability to withstand the film formation process.
[0168] <Manufacture and evaluation of backlight units> First, in order to manufacture a backlight unit, the following light emitting material composition and light diffusing layer coating liquid were prepared.
[0169] [Production of Light Emitting Material Composition] The curable compositions used in the production of the wavelength conversion member were mixed in the formulations shown in Table 4 to obtain curable light emitting material compositions 33 and 34. The appearances of the obtained compositions were visually observed, and the results are shown in Table 4.
[0170] [Table 4]
[0171] [Production of coating solution for light diffusion layer] Pentaerythritol triacrylate 30 parts (KAYARAD-PET-30, manufactured by Nippon Kayaku Co., Ltd.) · Urethane acrylate 70 parts (UV1700B, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) Photopolymerization initiator 5 parts (BASF, Irgacure 184) Silicone leveling agent 0.1 parts (Momentive Performance Materials, TSF4460) Acrylic resin diffusion particles 100 parts (Soken Chemical Industries, Ltd., Chemisnow KMR-3TA, average particle size 3 μm) Dilution solvent 500 parts (Methyl isobutyl ketone:cyclohexanone = 1:1 (mass ratio))
[0172] [Example 49, Comparative Example 14] On one side of a 12 μm thick biaxially oriented polyethylene terephthalate (PET) film, SiO X was evaporated to form an inorganic barrier layer having a thickness of 20 nm to prepare a barrier film. Next, a light diffusion layer coating solution having the following formulation was applied to one side of a 50 μm thick biaxially stretched PET film so that the thickness after drying would be 11 μm, and after drying, the film was irradiated with ultraviolet light to form a light diffusion layer, thereby producing a light diffusion film. Next, a biaxially stretched PET film having a thickness of 50 μm, the above-mentioned barrier film, and the light diffusion film were laminated in this order via an adhesive layer having a thickness of 3 μm to obtain a laminate sheet. The barrier film and the light diffusion film were attached so that the surfaces of the biaxially stretched PET film side of both films faced each other. The same process as above was repeated to obtain a total of two more laminate sheets. Next, the light-emitting material composition 33 or 34 shown in Table 4 was applied to the biaxially stretched PET film side of one of the laminate sheets so that the thickness after drying would be 100 μm, and after drying, the biaxially stretched PET film side of another laminate sheet was attached to the applied surface, and ultraviolet light (high pressure mercury lamp 120 W / cm) was applied from the light diffusion layer side of one of the laminate sheets. 2 Light, cumulative light output 1000mJ / cm 2 ) was applied to the light emitting material composition to cure it, thereby obtaining wavelength conversion members 29 and 30 each having a wavelength conversion layer.
[0173] A commercially available liquid crystal display device (7 inch diagonal) that uses a blue LED (450 nm) as the light source was disassembled and the backlight was removed. The backlight was an edge-light type, with a reflector below the light guide plate, a light diffusion film above the light guide plate, and two prism sheets. The two prism sheets had stripe lines that crossed at right angles between the lower and upper sheets. The light diffusion film was removed from the above backlight, and a wavelength conversion member 29 or 30 was placed between the light guide plate and the prism sheet to obtain a backlight. The backlight was prepared by placing a light guide plate so that one side of the light guide plate was the light entrance surface, and placing a wavelength conversion member and a prism sheet in that order on the light exit surface of the light guide plate, and further placing a reflective sheet on the back surface of the light guide plate to obtain backlight units 1 and 2. The backlight units were made to emit light, and the results of visually checking the color development are shown in Table 4.
[0174] According to the results in Table 4, the backlight unit having a wavelength conversion layer containing the luminescent material of the present invention having a specific ligand and a shell emitted white light (Example 49), whereas the backlight unit using the luminescent material not having a specific ligand and a shell did not function as a wavelength conversion layer and emitted blue light, which is the light source (Comparative Example 14).
[0175] In addition, composition 33, which is a mixture of two types of curable compositions, was transparent in the appearance evaluation, whereas composition 34 was slightly cloudy. This cloudiness is presumed to be due to a halogen exchange reaction between perovskite particles of different compositions. When a halogen exchange reaction occurs, the wavelength shifts and the composition changes rapidly, causing cloudiness and aggregation, which indicates that the luminescent nanoparticles are deactivated at the composition stage. On the other hand, composition 33 containing the luminescent material of the present invention has a core protected by a specific ligand and shell, so that the halogen exchange reaction is suppressed and each luminescent material is thought to exist independently in the composition.
[0176] In other words, since the luminescent material of the present invention itself has high stability, it can be applied to a wavelength converting material composition, and a wavelength converting member and a backlight unit using the composition, without being limited by the form of use.
[0177] Therefore, the luminescent material of the present invention, which has excellent luminescent properties and excellent stability, can be applied not only to light wavelength conversion components, but also to security inks that utilize a fluorescent response due to a specific wavelength, or electronic devices such as electroluminescent elements.
[0178] <Shell: Synthesis of compounds containing acidic groups> (Synthesis Examples 9-17: Copolymers (9)-(17)) Except for changing the monomers to the types and amounts shown in Table 5, the same procedure as in Synthesis Example 1 was carried out to obtain solutions of copolymers (9) to (17) containing repeating units derived from (meth)acrylic acid with a solid content concentration of 50%.
[0179] [Table 5]
[0180] <Production of Light Emitting Material Composition> [Examples 50 to 59] The same procedure as in Example 1 was carried out except that the copolymer (2) solution was changed to a solution of the copolymer shown in Table 6, to obtain light emitting material compositions 35 to 43.
[0181] <Evaluation of Light Emitting Material Composition> The obtained light emitting material-containing composition was evaluated in the same manner as in Example 1, except that the confirmation of the change over time in the light emitting characteristic evaluation was performed after 4 weeks. The results are shown in Table 6.
[0182] [Table 6]
[0183] The evaluation results revealed that by using a copolymer consisting of a monomer derived from (meth)acrylic acid, a monomer having an oxyalkylene group, and a (meth)acrylic acid alkyl ester monomer as the shell compound, the blue emitting material not only has excellent half-width and internal quantum efficiency, but also has further improved stability as a quantum dot.
[0184] <Manufacturing of wavelength conversion materials> [Examples 60 to 68] A light-emitting material composition, a polymerizable compound, a polymerization initiator, and a solvent were mixed according to the composition shown in Table 7 to obtain a curable composition. The obtained curable composition was spin-coated on a glass substrate (10 cm x 10 cm), and then dried at 80°C for 1 minute using a hot air dryer. Next, the coating was heated in a belt conveyor-type ultraviolet irradiator (high pressure mercury lamp 120 W / cm 2 Using a total light quantity of 400 mJ / cm 2 By irradiating the glass substrate with ultraviolet light so as to form a cured film with a thickness of 10 μm, wavelength conversion members 31 to 39 were obtained.
[0185] <Evaluation of wavelength conversion materials> The obtained wavelength conversion member was evaluated in the same manner as in Example 25. The results are shown in Table 7.
[0186] [Table 7]
[0187] According to the evaluation results, the wavelength conversion member using the luminescent material of the present invention exhibited the effect of suppressing deterioration over time of the appearance and deterioration over time of the external quantum efficiency, compared to wavelength conversion members using luminescent materials other than those of the present invention.
Claims
1. A luminescent material comprising: a core containing semiconductor nanoparticles having a perovskite crystal structure containing cesium lead halide; a ligand which is a saturated or unsaturated fatty acid sodium salt is introduced by ligand exchange into the core; and the core is further shell-coated with a copolymer; the saturated or unsaturated fatty acid sodium salt is at least one sodium salt selected from the group consisting of caproic acid, enanthic acid, caprylic acid, myristic acid, stearic acid and oleic acid; The copolymer contains, based on 100% by mass of monomers constituting the copolymer, 5 to 40% by mass of a monomer derived from (meth)acrylic acid, 5 to 40% by mass of an alkoxy polyalkylene glycol (meth)acrylate monomer, and 10 to 90% by mass of (meth)acrylic acid alkyl ester monomer, 1. The light-emitting material according to claim 1 ,
2. The luminescent material described in claim 1, wherein the saturated or unsaturated fatty acid sodium salt is a sodium salt of oleic acid.
3. 3. The light-emitting material according to claim 1, wherein the (meth)acrylic acid alkyl ester monomer has an alkyl chain having 6 to 30 carbon atoms.
4. 4. The light-emitting material according to claim 1, wherein the copolymer has a number average molecular weight of 1,000 or more and 15,000 or less.
5. A light-emitting material composition comprising the light-emitting material according to any one of claims 1 to 4 and a solvent.
6. A wavelength converting member having a wavelength converting layer which is a cured product of the light emitting material composition according to claim 5.
7. A backlight unit comprising at least the wavelength conversion member according to claim 6 and a light source.
8. A liquid crystal display device comprising at least the backlight unit according to claim 7 and a liquid crystal cell.
Citation Information
Patent Citations
Organic inorganic perovskite compound, light emitter, semiconductor material, electronic device and solar cell
JP2016132638A
Wavelength conversion material and its use
JP2017108129A
Perovskite / Polymer Composite Light-Emitting Materials, Manufacturing Methods and Applications
JP2018522959A
Luminescent crystal and its manufacture
JP2018530633A
Quantum dot, optical device using the same, and method of producing quantum dot
JP2019016772A